A Corpus-based Study of Tourism Destinations and Attractions in Indonesia - Sujatna, Eva Tuckyta Sari; Pamungkas, Kasno; Sujatna, Meita Lukitawati (E-Journal of Tourism, 2025)
While tourism has been widely studied across various disciplines, there is still limited research on the connection between tourism and corpus linguistics. The purpose of this study is to examine the types of tourism destinations and attractions in Indonesia by analyzing linguistic patterns in a large-scale corpus. The data source is the Leipzig Corpora Collection, comprising Indonesian language texts published between 2008 - 2018 (excluding 2014). Using the Master Plan of Indonesian Tourism Development 2010 - 2025 as a classification framework, this study identifies and categorizes tourism destinations and attractions based on occurrences of the word “ wisata ” ‘tourism’. The classification includes three categories: nature, culture, and man-made attractions. It is further divided into 10 classifications and 39 sub-classifications. The findings reveal that nature-based tourism is the most frequently mentioned category, comprising 499 instances (52%), followed by man-made attractions (38%), and cultural tourism destinations and attractions (10%). The most common reference made when talking about nature tourism is land-based tourism destinations and attractions, followed by marine waters, island, and geoparks. Through this research, we gain an understanding of how tourism destinations and attractions in Indonesia are represented linguistically and demonstrate the utility of corpus linguistics as a tool in tourism studies.